The Effect Customer Engagement and Corporate Reputation on Customer Loyality through Customer Satisfaction as a Mediating Variable - Adisaputra, Nurwakhid; Meiza, M. Andra; Curatman, Aang; Ayuningtyas, Farah Noor (International Journal of Business, Economics, and Social Development, 2025)
In the era of increasingly competitive e-commerce competition, customer loyalty is one of the main keys in maintaining business continuity. The phenomenon of low e-commerce user loyalty, as seen in a survey that shows 42% of users switch platforms for reasons of product availability, is a big challenge for industry players. This study aims to analyze the effect of customer engagement and corporate reputation on customer loyalty with customer satisfaction as a mediating variable, for Shopee e-commerce users in Indonesia.This study uses a quantitative approach with a survey method of 215 active Shopee user respondents. The data analysis technique used is Structural Equation Modeling (SEM) based on SmartPLS. The results showed that customer engagement and corporate reputation have a significant effect on customer loyalty, both directly and indirectly through customer satisfaction. Customer satisfaction proved to be a significant mediating variable in the relationship between customer engagement and corporate reputation on customer loyalty. These findings underscore the importance of an integrated strategy in increasing customer engagement, building a positive corporate reputation, and creating a satisfying customer experience to form sustainable loyalty